GuUGT, a glycosyltransferase from Glycyrrhiza uralensis, exhibits glycyrrhetinic acid 3- and 30-O-glycosylation. Issue 10 (9th October 2019) - Huang, Ying; Li, Da; Wang, Jinhe; Cai, Yi; Dai, Zhubo; Jiang, Dan; Liu, Chunsheng
Abstract : Glycyrrhiza uralensis is a well-known herbal medicine that contains triterpenoid saponins as the predominant bioactive components, and these compounds include glycyrrhetinic acid (GA)-glycoside derivatives. Although two genes encoding UDP-glycosyltransferases (UGTs) that glycosylate these derivates have been functionally characterized in G. uralensis, the mechanisms of glycosylation by other UGTs remain unknown. Based on the available transcriptome data, we isolated a UGT with expression in the roots of G. uralensis . This UGT gene possibly encodes a glucosyltransferase that glycosylates GA derivatives at the 3-OH site. Biochemical analyses revealed that the recombinant UGT enzyme could transfer a glucosyl moiety to the free 3-OH or 30-COOH groups of GA. Furthermore, engineered yeast harbouring genes involved in the biosynthetic pathway for GA-glycoside derivates produced GA-3- O -β-D-glucoside, implying that the enzyme has GA 3-O-glucosyltransferase activity in vivo . Our results could provide a frame for understand the function of the UGT gene family, and also is important for further studies of triterpenoids biosynthesis in G. uralensis .